#TITLE_ALTERNATIVE# - KASYFU AMBARA (NIM : 15110045 ) ; Pembimbing I : Dr. techn. Dudy D. Wijaya, S.T., M.Sc. ; Pem, AUZAN
The ionospheric slab thickness (τ) is an important parameter for studying the dynamic of the ionosphere. The slab thickness is often determined by a combination technique of Global Navigation Satellite System (GNSS) and ionosonde. However, this technique is not optimal due to the sparsely populated of ionosonde stations in Indonesia. The purposes of this research is to optimize the use of single GNSS receiver to determine the ionospheric slab thickness without receiving any help from other techniques, to validate the results with a combination technique of Global Navigation Satellite System (GNSS) and ionosonde, and to study its physical characteristics. The method which is used in this research is a new approach from the improvement of geometric-free formula called Improved Geometric Free (IGF). The IGF formula is then applied to determine the slab thickness in 2011 and 2012 by using IGS (International GNSS Service) station data which is managed by BIG (Geospatial Information Agency). The validation results obtained correlation values between the two methods in 2011 and 2012 were 0.64 and 0.60, and the RMS deviations were 155.51 km and 210.19 km. The category correlation concluded that the ionospheric slab thickness which is obtained from the single GNSS receiver is relevant to be applied for ionospheric slab thickness (τ) study. Finally, by analyzing the data of the ionospheric slab thickness in 2011 and 2012, the physical characteristics of daily, seasonal, and correlation with the physical characteristics of the sunspot number could be acquired.